Parental mediation in the use of screens by children and adolescents: a systematic literature review - Julia Flaibam Giovanelli; Laura Soares da Silva; Wanderlei Abadio de Oliveira; Adriana Scatena; Fernando Ferreira Semolini; André Luiz Monezi Andrade (Ciencias Psicológicas)
Parental mediation is essential for guiding the appropriate use of devices, aiming to minimize potential negative impacts such as anxiety, depression, and low self-esteem. This systematic review investigated the influence of different parental mediation styles on the use of digital media by children and adolescents. A new method for searching and classifying articles was used, employing the ASReview software, which utilizes a machine learning model to enhance the efficiency and accuracy of article selection. The review followed all procedures required by PROSPERO. Initially, 28,964 articles were identified, and based on ASReview, 359 articles were read, of which 27 were included in the study. The quality of the manuscripts was assessed using the Critical Appraisal Checklist for Analytical Cross-Sectional Studies. The main findings indicated that parental mediation is a significant protective factor against excessive internet use, gaming dependence, and cyberbullying. Active and restrictive mediation strategies proved effective in moderating the relationship between digital media use and mental health outcomes, highlighting the critical role of parents in guiding their children's digital consumption.